2007
DOI: 10.1017/s0950268807009156
|View full text |Cite
|
Sign up to set email alerts
|

Understanding, compliance and psychological impact of the SARS quarantine experience

Abstract: This study examines a cohort of persons quarantined during the 2003 SARS outbreak in Canada and describes their understanding of, difficulties and compliance with, and the psychological impact of the quarantine experience. A mailed questionnaire was administered to 1912 eligible adults and included the Impact of Events Scale - Revised (IES-R) to assess symptoms of post-traumatic stress disorder (PTSD). Self-reported compliance with all required quarantine measures was low (15.8+/-2.3%), although significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
706
5
64

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 818 publications
(866 citation statements)
references
References 12 publications
54
706
5
64
Order By: Relevance
“…Our findings was echoed in the study by other two similar studies that perceived risk of fatality was one of the main predictor for HCW’s consideration of leaving their job (Shaio et al. 2007, Reynolds et al. 2008).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our findings was echoed in the study by other two similar studies that perceived risk of fatality was one of the main predictor for HCW’s consideration of leaving their job (Shaio et al. 2007, Reynolds et al. 2008).…”
Section: Discussionsupporting
confidence: 74%
“…Findings from the Taiwan study showed that, although HCWs may not be necessarily needed to be informed of all the information on the epidemic, they wanted to be kept in the communication loop and to be reassured when information and equipment became available (Tsai & Ya‐Ti 2008). On the contrary, belief in the effectiveness of personal protective equipment was not an important factor for HCW’s consideration of leaving their job (Reynolds et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…146 Compliance with quarantine measures was low during the 2003 SARS crisis in Canada and this measure caused psychological distress. 147 Given the costs and the uncertainty of the effectiveness of nonpharmaceutical control measures such as face masks and quarantine, there is an urgent need for further empirical and theoretical research on the transmission pathways of influenza viruses.…”
Section: Discussionmentioning
confidence: 99%
“…All other quantitative studies only surveyed those who had been quarantined and generally reported a high prevalence of symptoms of psychological distress and disorder. Studies reported on general psychological symptoms, 22 emotional disturbance, 34 depression, 16 stress, 15 low mood, 18 irritability, 18 insomnia, 18 posttraumatic stress symptoms 25 (rated on Weiss and Marmar's Impact of Event Scale-Revised 35 ), anger, 20 and emotional exhaus tion. 21 Low mood (660 [73%] of 903) and irritability (512 [57%] of 903) stand out as having high prevalence.…”
Section: The Psychological Impact Of Quarantinementioning
confidence: 99%